Real-Time Hierarchical Resource Allocation - Timothy Van Zandt (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
This paper presents a model that distinguishes between decentralized information processing and decentralized decision making in organizations; it shows that decentralized decision making can be advantageous due to computational delay, even in the absence of communication costs. The key feature of the model, which makes this result possible, is that decisions in a stochastic control problem are calculated in real time by boundedly rational members of an adminstration staff. The decision problem is to allocate resources in a changing environment. We consider a class of hierarchical procedures in which information about cost functions flow down and are disaggregated by the hierarchy. Nodes of the hierarchy correspond not to a single person but to decision-making units within which there may be decentralized information processing. The lower tiers of multitier hierarchies can allocate resources quickly within small groups, while higher tiers are still able to exploit gains from trade between the groups (although on the basis of older informations).
Keywords: D83; D23; 330; decentralization; hierarchies; bounded rationality; real-time control